Introduction - Jia-Rey Chang (A+BE: Architecture and the Built Environment, 2018)
This research examines three fundamental topics: Computation, Embodiment, and Biology to develop a design framework for developing Organic, Interactive Architectures. The design framework is termed “HyperCell”, which involves, developing real-time interactive designs leading to novel organic architectural proposals. Furthermore, such a biotic space advances the next level of artistic and philosophical discourse via broadening the range of innovative interactive architectural design thinking. The ultimate goal of the research is to evoke and enrich more innovative interactive architectural design to take place in the near future.